Upaya Perlindungan Tanah Pertanian Terdampak Ganti Rugi Akibat Pengadaan Tanah Untuk Kepentingan Umum (Studi Kasus: Yogyakarta International Airport) - Aiska, Gitta Sabilla; Koeswahyono, Imam; Nurhayati, Prawatya Ido (WARKAT, 2022)
This research aims to study the protection of agricultural lands regarding land procurement and airport development that has taken place since the issuance of the Decree of the Governor of Yogyakarta Number 68/KEP/2015 on 31 March 2015. This has left impacts on some farmers who have lands, sharecroppers, and peasants. On the other hand, Article 36 of Law Number 2 of 2012 concerning land procurement for the development of public facilities states that compensation can be given in the form of a. money, b. substituting land; c. substituting residence; d, share ownership; or e, another form of compensation agreed by the two parties. This does not ensure that the right holders can freely choose the form of compensation needed. This research employed empirical and socio-juridical methods involving direct observation to gain data that revealed the impacts and measures of protecting agricultural lands. The data were obtained by conducting interviews with Regional Land and Spatial Planning Agency, National Land Agency, the sub-district office, and affected farmers. The data were analyzed based on descriptive qualitative methods, revealing that the measures taken to protect agricultural lands in the case of giving compensation in land procurement for public facilities are not appropriately implemented. This is obvious in the observation results, reporting that the compensation given still leaves impacts on the farming community.